2013
DOI: 10.1159/000351653
|View full text |Cite
|
Sign up to set email alerts
|

New-Generation Multifocal Intraocular Lens for Pediatric Cataract

Abstract: Background/Aims: To evaluate multifocal intraocular lens (MIOL) implantation in children. Methods: This is a retrospective study evaluating refractive, visual and safety results of MIOL in pediatric cataract surgery. Average follow-up was 25.73 ± 10.5 months. Surgery included 12 o'clock clear corneal incision, anterior capsulorhexis, lens material aspiration and MIOL implantation (SN6AD3; Alcon). Results: We included 34 cataract eyes of 26 pediatric patients aged 2-15 years, of which 14 (54%) were unilateral. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Previous articles evaluated the safety and efficacy of multifocal IOLs in children affected by infantile cataract older than 2 years, showing they could represent a safe alternative to monofocal pseudophakia, providing visual acuity improvement and, mainly in bilateral cases, stereopsis, with a very low complication rate. 14–16…”
mentioning
confidence: 99%
“…Previous articles evaluated the safety and efficacy of multifocal IOLs in children affected by infantile cataract older than 2 years, showing they could represent a safe alternative to monofocal pseudophakia, providing visual acuity improvement and, mainly in bilateral cases, stereopsis, with a very low complication rate. 14–16…”
mentioning
confidence: 99%
“…Improvement in CDVA was seen in 70–100% of the patients in the majority of the studies. 6, 7, 37 The rate of spectacle independence for near was found to be comparable in most of the studies ranging from 70–80% in bilateral cases. 6 One of the first prospective studies by Jacobi et al .…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 77%
“…Most of the series on multifocal IOLs used either clear corneal or limbal based incisions for entry and lens aspiration with or without a posterior capsulotomy and anterior vitrectomy depending on the age of the patient followed by IOL implantation. Patients less than 5 years underwent posterior curvilinear capsulorhexis (PCCC) in one series 37 and this age limit was kept as 8 years in another series. 6 Posterior capsulotomy was performed in 60–100% participants 7, 33 ; leaving the capsule intact was invariably seen to be associated with PCO formation.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%
“…Patients yielded good results for distance and near vision and improvement in stereopsis with low complication rates. 17 In both studies the authors concluded that the implantation of MIOLs is a viable alternative to monofocal IOL implantation in pediatric cataract cases. 4 , 17 …”
Section: Discussionmentioning
confidence: 97%